Menguak Perbedaan: Regulasi Pidana Mati dalam Sejarah Hukum Indonesia dari Tahun 1946 hingga 2023 - Herman Balla; Iswandy Rani Saputra; Jumadi S; Siswanto Siswanto (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
The study compares the regulations regarding the death penalty between the Indonesian Criminal Code and Law Number 01 of 2023 concerning the Criminal Code. Utilizing a normative juridical research method, which relies on library literature including laws and scientific works, the research analyzes primary, secondary, and tertiary legal data. Under Law No. 02/PNPS/1964, executions are carried out by firing squad. Key differences highlighted include the possibility of converting the death penalty to life imprisonment after ten years of good behavior, the reclassification of the death penalty as an alternative punishment rather than a basic criminal category, and specific provisions for pregnant women, breastfeeding mothers, and mentally ill individuals in the National Criminal Code. The new regulations emphasize human rights and reflect a more modern approach aligned with Indonesian legal culture.